Postrzeganie języka angielskiego przez polskich i litewskich studentów: wnioski dla uczelni wyższych = The perception of English by Polish and Lithuanian university students: implications for higher education - Karczewska, Małgorzata; Žegunien?, Vaida (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It cannot be denied that English has a special status in today`s world, being used in international com?munication in both professional and private life. In order to have an insight into how the influence of English on other languages and its role in creating global awareness are indeed perceived, a study among Polish and Lithuanian university students was conducted. Answers to the questions included in the survey are presented in a comparative Polish - Lithuanian key in order to trace similarities and differences between the respondents in two European countries which joined the European Union in 2004 and has been fast developing since then.
Keywords: język angielski globalny; nauczanie języków; szkolnictwo wyższe; Polska; Litwa; global English; language teaching; higher education institutions; Poland; Lithuania